Effects of the phenological stage, type of cutting and plant growth regulators on the propagation by stem cutting of Poiretia latifolia Vogel, a brazilian native medicinal plant - Verdi, Rovier; Bettoni, Jean Carlos; Werner, Simone Silmara; Boff, Mari Inês Carissimi; Boff, Pedro (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
Poiretia latifolia Vogel has bioactive potential that includes antibiotic properties for human uses. The aim of this research was to develop an efficient method for vegetative propagation of P. latifolia by using cuttings as an aid to the selection and multiplication of interesting genotypes. In the first experiment, the cuttings were collected in vegetative and reproductive stages and treated with six plant growth regulators and distilled water. In the second experiment, the treatments consisted of cuttings from the apical, median, and basal branch segments. The treatment with the immersion of cuttings in 4,000 mg L-1 of IBA provided greater number and length of the roots, while high dilution of Calcarea phosphorica at 20CH produced longer branches. The cuttings of the middle and basal part of the branch were found to be more viable. It was achieved 79.17% of cuttings rooting using Calcarea phosphorica 20CH. The vegetative propagation employed in this work is a feasible option for the domestication, preservation, and cultivation of Poiretia latifolia.